Association of c.56C > G (rs3135506) Apolipoprotein A5 Gene Polymorphism with Coronary Artery Disease in Moroccan Subjects: A Case-Control Study and an Updated Meta-Analysis. (4th August 2020) - Morjane, Imane; Charoute, Hicham; Ouatou, Sanaa; Elkhattabi, Lamiae; Benrahma, Houda; Saile, Rachid; Rouba, Hassan; Barakat, Abdelhamid
Abstract : Purpose . Coronary artery diseases (CAD) are clinical cardiovascular events associated with dyslipidemia in common. The interaction between environmental and genetic factors can be responsible for CAD. The present paper aimed to examine the association between c.56C > G (rs3135506) APOA5 gene polymorphism and CAD in Moroccan individuals and to perform an association update meta-analysis. Materials and Methods . The c.56C > G variant was genotyped in 122 patients with CAD and 134 unrelated controls. Genetic association analysis and comparison of biochemical parameters were performed using R statistical language. In addition, a comprehensive meta-analysis including eleven published studies in addition to our case-control study results was conducted using Review Manager 5.3. Publication bias was examined by Egger's test and funnel plot. Results . The case-control study data showed that the c.56C > G polymorphism was associated with CAD susceptibility under codominant (P -value = 0.001), recessive (P -value <0.001) and log-additive (P -value = 0.008) inheritance models. In addition, this polymorphism was significantly associated with increased levels of systolic and diastolic blood pressures, triglycerides, glycemia, and total cholesterol. Furthermore, meta-analysis showed a significant association between the c.56C > G gene polymorphism and increased risk of CAD under recessive (OR = 3.39[1.77–6.50], P value <0.001) and homozygote codominant (OR = 3.96[2.44–6.45], P value <0.001) models. Conclusion . Our case-control study revealed a significant association between c.56C > G polymorphism and CAD in the Moroccan population. In addition, meta-analysis data supported the implication of this polymorphism in CAD susceptibility.